Sleep Disruption in Parents of Children with Atopic dermatitis: A Cause of Concern - Kansal, Naveen Kumar; Chawla, Omna (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Abstract It is well-established that the physical, mental, and cognitive health of an individual depends on proper sleep. However, regular sleep patterns are likely disrupted in persons who care for persons with chronic illnesses. Atopic dermatitis is a common, chronic inflammatory cutaneous disease affecting a sizeable proportion of the pediatric population. Most parents experience stress while caring for atopic dermatitis in their children. It is a time-intensive and emotionally demanding situation that adversely affects sleep and leads to exhaustion and worry. Sleep disruption of parents further contributes to difficulty coping with dermatitis management and parenting demands. This brief review aims to identify the extent and nature of sleep disruption in parents of atopic children and interventions to address the same.